Menghayati Kehadiran Riil Kristus, Tubuh dan Darah-Nya, dalam Perayaan Ekaristi - Bernardus Teguh Raharjo; Firalen Vianney Ngantung (Sekolah Tinggi Filsafat Seminari Pineleng, 2020)
The essay deals with the theological discussion about the real presence of Christ in the eucharist celebration. According the Roman Catholic understanding, as the presiding priest pronounces the verba Domini (the word of the Lord) during the eucharistic prayer, the bread and wine are consecrated and changed substantially into the Body and Blood of Christ. Christ is present in reality with all His deity and humanity in consecrated bread and wine. In the Catholic dogmatic it is called a transubstantiation. The Church’s faith in the real presence of Jesus is celebrated in Eucharist. This celebration of faith based on the institution of Jesus Christ himself at the Last Supper. In the Eucharist, bread and wine are changed into the Body and Blood of Christ, trough the words of Christ (consecration) and the prayer to the Holy Spirit (epiclesis). Awareness and understanding of the real presence of Christ, God, in the Eucharist build a liturgical sense of the faithful to express the proper liturgical attitude.